(untitled) (Symposium on Life and Environmental Sciences, 2026)
This paper presents the development of an intelligent automated water quality monitoring system based on the Arduino microcontroller platform. The proposed system is designed for continuous real-time monitoring of the key physicochemical parameters of water using temperature, pH, turbidity, and water level sensors. Measurement data are transmitted via a GSM communication module, enabling remote monitoring of water bodies and rapid notification of users when abnormal conditions are detected. The developed system is characterized by low implementation cost, ease of operation, high flexibility, and adaptability to various application areas, including agriculture, water supply systems, aquaculture, and environmental monitoring. Experimental evaluation confirmed the reliability of the proposed hardware–software solution, the accuracy of sensor measurements, and the effectiveness of remote data transmission. The proposed intelligent monitoring system represents an affordable and efficient solution for continuous environmental surveillance and sustainable water resource management.